Penerapan Ekonomi Hijau Dan Akuntansi Lingkungan Dalam Strategi Bisnis PT. Surabaya Industrial Estate Rungkut (SIER) - Yohana Natalia Cristati; Windiana Wahyu Ekaputri; Wandira Regita Putri Cahyani; Maria Yovita R. Pandin (Jurnal Mutiara Ilmu Akuntansi, 2024)
Surabaya Industrial Estate Rungkut (SIER) is a company that develops and manages industrial estates located in Surabaya, East Java, Indonesia. Established in 1991, PT. SIER has become one of the important industrial centers in the East Java region. The main focus of PT. Surabaya Industrial Estate Rungkut (SIER) is to provide complete and high-quality infrastructure to support various types of industries, ranging from manufacturing to logistics. The purpose of this research is to analyze the implementation of green economy and environmental accounting in the business strategy of PT. Surabaya Industrial Estate Rungkut (SIER), an industrial estate development company in Surabaya, Indonesia. Green economy and environmental accounting are important approaches for companies to achieve sustainability goals and corporate social responsibility.